2022
DOI: 10.2196/31929
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Literature Search of Digital Health Technology Use in Neurological Conditions: Review of Digital Tools to Promote Self-management and Support

Abstract: Background The use of digital health technology to promote and deliver postdiagnostic care in neurological conditions is becoming increasingly common. However, the range of digital tools available across different neurological conditions and how they facilitate self-management are unclear. Objective This review aims to identify digital tools that promote self-management in neurological conditions and to investigate their underlying functionality and sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Digital health technologies can record, store and report healthcare information that can then be used to promote self-management and/or facilitate HCP communication, with the ultimate aim of enhancing patient care. 6 They can reduce patient barriers (distance, time, costs) while also improving the efficiency of healthcare delivery. 7 MSGo has been designed to provide a seamless digital platform accessible by HCPs (MSGo HCP Portal, HCP App) and pwSPMS (MSGo Patient App), with the aim of integrating data into formal clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Digital health technologies can record, store and report healthcare information that can then be used to promote self-management and/or facilitate HCP communication, with the ultimate aim of enhancing patient care. 6 They can reduce patient barriers (distance, time, costs) while also improving the efficiency of healthcare delivery. 7 MSGo has been designed to provide a seamless digital platform accessible by HCPs (MSGo HCP Portal, HCP App) and pwSPMS (MSGo Patient App), with the aim of integrating data into formal clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the web‐based information may be of varying quality, 30 especially if did not originate from specialized epilepsy centers 31 . Electronic epilepsy self‐management platforms have shown promise to improve self‐efficacy and medication adherence, but there remains a gap in evaluating the effectiveness of these tools once adopted by patients 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…31 Electronic epilepsy self-management platforms have shown promise to improve self-efficacy and medication adherence, but there remains a gap in evaluating the effectiveness of these tools once adopted by patients. 32,33 Overall, the main driver of eHealth behaviors was technological access (frequency of computer use and access to the internet), which has been well documented, and sociodemographic characteristics (female sex, higher education). We found that higher education was associated with frequent eHealth activity, which has previously been reported to be predictive of online patient-provider communication and general eHealth use 34,35 as well as general preventative health care use.…”
Section: Discussionmentioning
confidence: 99%
“…31 The ability, experience and intuition of medical professionals to translate knowledge based on collective decision-making to individual decision-making is crucial to the much-needed customization of medicine. 32 Within 20 years, such individual therapeutic decisions will be substantially backed by digital technologies, creating a new healthcare ecosystem that is frequently referred to as "digital medicine." 33 New "digital health pathways" or data-driven personalized decision support, which is based on a combination of multimodal data sources, including evidence-based medical knowledge, is anticipated to be part of the next phase of digitalization (e.g., clinical guidelines).…”
Section: Introductionmentioning
confidence: 99%